Drying Kinetics of Cassava and Orange-Fleshed Sweet Potato and The Physico-Nutritional Characterization of Their Composite ‘Fufu’ Flours - Younge Samuel (University of Cape Coast, 2022)
In an effort to address illnesses caused by a lack of vitamin A, the orangefleshed sweet potato (OFSP) is being pushed for eating as a public health tool in Ghana. As a staple diet in many households, ‘fufu’ can be suitably fortified with OFSP for the delivery of its essential micronutrients for health improvement. In this study, the drying characteristics of cassava pulp and orange-fleshed (OFSP) sweet potato chips for processing into ‘fufu’ flours and the moisture sorption behaviour of the composite flour blends were investigated. Also, the nutritional and functional characteristics of composite cassava/OFSP flour blends were examined. The composite flour blends were then cooked into ‘fufu’ and subjected to sensory evaluation using the ninepoint hedonic scale. The pulverized cassava pulp was dried at 70 oC while the OFSP chips were dried at 60 oC. The initial average moisture content of the pulverized cassava pulp was 0.07 kg water/kg dry matter and was dried to 8.9 x 10-5 kg water/kg dry matter in 6 h while the OFSP chips was also dried from 0.6 kg water/kg dry matter to 9.0 x 10-5 kg water/kg dry matter in 9 h. The drying curves showed a single falling rate period for both samples. The effective moisture diffusivity for cassava was 2.36 x 10-8 m2/s and that for OFSP was 4.60 x 10-8 m2/s, both being within the range for drying agricultural food commodities. The Page model best described the drying characteristics of both cassava and OFSP samples. The moisture sorption isotherm curves for the various composite flour blends showed a sigmoidal plot that was typical of type II isotherms for starchy foods. The GAB model also best described the moisture sorption behaviour of the various composite blends. OFSP significantly (p ˂ 0.05) enriched the nutritional and functional properties as itssubstitution levels for cassava increased. However, the elastic texture and pasting properties degraded. Beyond 5% substitution of cassava with OFSP, sensory panelists disliked the organoleptic properties of the ‘fufu’ due to the high soluble sugar and fat in OFSP which affected the ‘fufu’ texture (elasticity). The low level of microbial count with no detection of aflatoxin strains in the flours signified how the fortified ‘fufu’ flour was safe for consumption. Shelf-life analysis after six months also showed that betacarotene content in the most preferred flour sample packaged in the polyethylene-laminated paper bag was high to serve its nutritional purpose. Overall, this study showed a high potential of OFSP substitution for cassava in the production of ‘fufu’ to improve its nutritional value. The adoption of this OFSP-based food product will help diversify the uses of OFSP and also provide an alternative healthy and nutritious food for addressing vitamin A deficiency diseases in Ghana and Africa at large.
xx,294p:,ill
Keywords: Beta-carotene Cassava Drying kinetics Fufu Orange-fleshed sweet potato Vitamin A deficiency